2020
DOI: 10.1038/s41561-020-0593-2
|View full text |Cite
|
Sign up to set email alerts
|

Global distribution of sediment-hosted metals controlled by craton edge stability

Abstract: An improved and extended internally consistent thermodynamic dataset for phases of petrological interest, involving a new equation of state for solids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
155
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(208 citation statements)
references
References 122 publications
6
155
1
Order By: Relevance
“…Since our primary objective is to obtain an accurate V S -to-density parameterization for fertile oceanic mantle, we have chosen to omit these separate continental constraints. Nevertheless, it has been shown that continental geotherms calculated using our ocean-only approach provide a good match to Australian paleogeotherms that in some cases are over a billion years old (Hoggard et al, 2020b).…”
Section: 1029/2019jb019062mentioning
confidence: 90%
“…Since our primary objective is to obtain an accurate V S -to-density parameterization for fertile oceanic mantle, we have chosen to omit these separate continental constraints. Nevertheless, it has been shown that continental geotherms calculated using our ocean-only approach provide a good match to Australian paleogeotherms that in some cases are over a billion years old (Hoggard et al, 2020b).…”
Section: 1029/2019jb019062mentioning
confidence: 90%
“…The Australian continental crust has an overall westward age progression from dominantly Phanerozoic in the east, dominantly Proterozoic in the center and dominantly Archean in the west (Figure 1). Previous lithospheric scale studies have recognized changes in the lithospheric thickness and physical properties (temperature and composition), according to fundamental boundaries at 140–145°E and 120–125°E (Aitken et al, 2015; Fishwick et al, 2005, 2008; Hoggard et al, 2020; Kennett et al, 2004; Yoshizawa, 2014; Yoshizawa & Kennett, 2015). However, these boundaries do not clearly define thermal and compositional trends, nor a clear distinction between Archean and Proterozoic lithospheres.…”
Section: Introductionmentioning
confidence: 99%
“…Goes et al (2005) identified an average trend of increasing temperature with decreasing thermo‐tectonic age and a large thermal variability (200–700°C), by inverting S‐velocity models into mantle temperatures. Xenoliths data revealed thermal perturbations associated with volcanic episodes in Eastern Australia, while the Archaean and Proterozoic areas in Western Australia show typically low temperatures (Hoggard et al, 2020; O'Really et al, 1997). Joint interpretation of the thermo‐compositional structure of the Australian Continent has been recently made by Khan et al (2013), who applied a Markov Chain Monte Carlo method, using the global surface wave phase‐velocity maps of Visser et al (2008).…”
Section: Introductionmentioning
confidence: 99%
“…noted a similar relationship between craton margins and the Precambrian IOCG 'sensu stricto' deposits; the current investigation supports this proposal with additional provinces and data. Furthermore, in Australia this spatial relationship has been shown more precisely by Hoggard et al (2020) who demonstrated that the large Cu-Au deposits of the eastern Gawler Craton and the Cloncurry provinces lie within ~100 km of the surface projection of the 170 km depth contour of the lithosphere-asthenosphere boundary (LAB). The same spatial association of the LAB with the Cu-Au-Fe deposits considered in the present review is evident globally (Czarnota, Hoggard, Skirrow, in prep.…”
Section: Global Distributionmentioning
confidence: 87%